Cultural Conservatism - Morin, Olivier (Journal of cognition and culture, 2022)
Trying to preserve cultural forms as faithfully as possible is a key motivation for cultural transmission. This paper reviews two possible accounts of it. One, evolutionary conservatism, is premised on the superiority of accumulated cultural knowledge compared to individual judgement – a theme that runs strongly through both the cultural evolution literature and conservative political philosophy. I argue for a clear distinction between evolutionary conservatism, and status quo conservatism as motivated by loss- and risk-aversion. I proceed to tackle some outstanding issues regarding status quo conservatism: its association with attachment to social hierarchies; the kind of cultural practices that tend to elicit it; and the question why an attitude motivated by considerations of costs and benefits might be manifested as a rigid or absolute principle. Seeing some cultural practices as equilibria in a coordination game helps answer these questions.